1990
DOI: 10.1007/bf01342753
|View full text |Cite
|
Sign up to set email alerts
|

The validity of vigilance tasks in differential diagnosis of children referred for attention and learning problems

Abstract: This study was conducted to evaluate the convergent and discriminant validity of vigilance measures of attention and impulsivity in children. One hundred children referred for evaluation of attention and learning problems were administered a battery of tests including two vigilance tasks, other laboratory measures of inattention and impulsivity, and parent and teacher ratings. It was predicted that vigilance task performance would correlate with teacher ratings and laboratory measures of inattention while corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
2
1

Year Published

1992
1992
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 34 publications
2
9
2
1
Order By: Relevance
“…The results of the present study are inconsistent, however, with the results of work by Aylward, Gordon, and Verhulst (1997), Klee and Garfinkel (1983), Lovejoy and Rasmussen (1990), and Seidel and Joschko (1991). These four studies found a significant relationship between CPT performance and intelligence, but only between the ability to detect the target (errors of omission) and the intellectual measures that purportedly measure attention (Arithmetic subtest or FD factor).…”
Section: Discussioncontrasting
confidence: 80%
“…The results of the present study are inconsistent, however, with the results of work by Aylward, Gordon, and Verhulst (1997), Klee and Garfinkel (1983), Lovejoy and Rasmussen (1990), and Seidel and Joschko (1991). These four studies found a significant relationship between CPT performance and intelligence, but only between the ability to detect the target (errors of omission) and the intellectual measures that purportedly measure attention (Arithmetic subtest or FD factor).…”
Section: Discussioncontrasting
confidence: 80%
“…Earlier studies suggested that children with superior IQs made fewer errors due to a ceiling effect 18,23. In similar findings, intelligence potentially affected CPT performances of the child and adolescent patients in psychiatric hospitals36 and also of patients with attention and learning problems 37…”
Section: Discussionmentioning
confidence: 68%
“…Increased errors over trials did occur for the ADHD group in the conjunction baseline, but this may be due to aversion to delay (see above) rather than sustained attention difficulties. This finding can therefore be added to the studies that fail to show decrements in performance over time in this population (e.g., see van der Meere & Sergeant, 1988; Lovejoy & Rasmussen, 1990; Corkum & Siegel, 1993; Slusarek, Velling, Bunk, & Eggers, 2001, for examples).…”
Section: Errorsmentioning
confidence: 90%